Exploring Students’ Target and Learning Needs in Developing English Speaking Skills: A Study at MTs Miftahul Lubab Ngawi - Sa’diyah , Ma’rifatul Halimatus; Sukarno (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study investigates the pragmatic analysis of expressive utterances in celebrities’ apology posts on Instagram. It examines the types and functions of direct and indirect expressive speech acts and those in apologies. It applied qualitative descriptive research with data from celebrity Instagram posts that grew significant community attention within five years (2021-2025). The data analysis involved categorizing each apology utterance as either direct or indirect and subsequently identifying its pragmatic function within the specific context of the celebrity's post. The findings show that celebrities tend to use a combination of direct and indirect apology expressions. Direct apologies, such as “I apologize” and “I’m sorry,” indicate clear responsibility, while indirect expressions, such as “I feel greatly ashamed of myself” and “I deeply regret my behavior,” create sympathy and reduce negative impact. These findings hint at the nature of online communication on social media sites and the importance of apologetic strategies for keeping these relationships harmonious with the general public and enhancing a positive image for celebrities.